Spontaneous Second Intercostal Artery Bleeding Complicated with Massive Hemothorax after Lower Limb Angioplasty Procedure (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.
Keywords: Pulmonology; Case Report